2011
DOI: 10.1111/j.1365-246x.2011.05110.x
|View full text |Cite
|
Sign up to set email alerts
|

Seismic response of a single and a set of filled joints of viscoelastic deformational behaviour

Abstract: S U M M A R YRock joints are often filled with weak medium, for example, saturated clay or sand, of viscoelastic nature. Their effects on wave propagation can be modelled as displacement and stress discontinuity conditions. The viscoelastic behaviour of the filled joint can be described by either the Kelvin or the Maxwell models. The analytical solutions for wave propagation across a single joint are derived in this paper by accounting for the incident angle, the nondimensional joint stiffness, the non-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…In the DSDM (Zhu et al, 2011), for a rock fracture filled with dry sand, the Kelvin model, consisting of one spring and one dashpot in parallel, can be adopted to describe the dynamic response of the filled fracture. The specific viscosity is set to zero for a fracture filled with dry sand.…”
Section: Analytical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the DSDM (Zhu et al, 2011), for a rock fracture filled with dry sand, the Kelvin model, consisting of one spring and one dashpot in parallel, can be adopted to describe the dynamic response of the filled fracture. The specific viscosity is set to zero for a fracture filled with dry sand.…”
Section: Analytical Modelsmentioning
confidence: 99%
“…Meanwhile, the thickness of filling materials may not be overlooked compared with the wavelength. A newer and more precise model to describe the boundary conditions of a filled fracture, the displacement and stress discontinuity model (DSDM), has been developed by Zhu et al (2011). It proposes that the stress discontinuity across a filled fracture is caused by the specific initial mass of filling materials and the displacement discontinuity is determined by the transmitted stress and the specific fracture stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…By modeling the interface between two solids as a thin viscoelastic layer with stiffness and inertia term, wave propagation was addressed by Rokhlin and Wang (1991). Later, the thin viscoelastic layer interface concept was extended by Zhu et al (2011) to study wave propagation across filled joints. The results from Rokhlin and Wang (1991), Li et al (2010) and Zhu et al (2011) showed that the thickness of a filled joint influences wave propagation in a rock mass.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the thin viscoelastic layer interface concept was extended by Zhu et al (2011) to study wave propagation across filled joints. The results from Rokhlin and Wang (1991), Li et al (2010) and Zhu et al (2011) showed that the thickness of a filled joint influences wave propagation in a rock mass. In practical situation, when a stress wave propagates across a filled joint with one thin thickness, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Stress wave propagation across rock joints has been investigated theoretically (e.g., Pyrak-Nolte et al 1990;Cai and Zhao 2000;Li et al 2010a;Zhu et al 2011) and experimentally (e.g., Leucci and Giorgi 2006;Zhao et al 2006Zhao et al , 2008Li et al 2010b). Many studies focus on the interaction between the stress wave and the rock joints (e.g., Li et al 2011;Ma et al 2011).…”
Section: Introductionmentioning
confidence: 99%